2002
DOI: 10.1046/j.1365-246x.2002.01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous inversion of steep-angle observations ofPcPandScPin Europe-what can we learn about the core-mantle boundary?

Abstract: Summary At epicentral distances less than 30°, the steep‐angle reflections PcP and ScP from the core–mantle boundary (CMB) are normally difficult to identify and rarely reported. The reason is that the reflection coefficient at the CMB for these phases is relatively small and PcP and ScP onsets are often disturbed by interference with other more prominent phases. However, the absolute traveltimes of PcP and ScP in the steep‐angle range are the most sensitive seismic phases for depth undulations of the CMB and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Even so, it is difficult to separate these two contributions. As noted by Schweitzer (2002), the data may be explained as well by seismic source perturbations or mantle heterogeneities, rather than by CMB undulation. This phase is unfortunately difficult to observe and rarely reported in the bulletins.…”
Section: The Topography Of the Cmbmentioning
confidence: 70%
“…Even so, it is difficult to separate these two contributions. As noted by Schweitzer (2002), the data may be explained as well by seismic source perturbations or mantle heterogeneities, rather than by CMB undulation. This phase is unfortunately difficult to observe and rarely reported in the bulletins.…”
Section: The Topography Of the Cmbmentioning
confidence: 70%
“…The strength of the topographic coupling depends on the amplitude ( h ) and angular order ( m ) of the topographic variations. Seismic studies have found that it is difficult to separate the influence of CMB topography from other effects (e.g., lateral heterogeneity within D″) using the available data [e.g., Garcia and Souriau , 2000; Schweitzer , 2002; Sze and van der Hilst , 2003]. Despite this difficulty it is possible to place bounds on the amplitude of CMB topography and hence constrain the importance of topographic coupling.…”
Section: Resultsmentioning
confidence: 99%
“…An apparent anticyclonic rotation of roundly 800 years of main the period (half rotation in around 400 years) is evident. Also a recent acceleration of the motion is visible undulations of peak-to-peak value of around 24 km (GARCIA and SOURIAU, 2000) or less: 12 km (e.g., SCHWEITZER, 2002) or even 3 km (e.g., BOWIN, 1986;SZE and VAN DER HILST, 2003).…”
Section: Equivalent Monopole Source Analysis Of the South Atlantic Anmentioning
confidence: 99%